Cancer registries in Africa 2014: A survey of operational features and uses in cancer control planning. Issue 9 (1st November 2015) - Gakunga, Robai; Parkin, D. Maxwell; On behalf of the African Cancer Registry Network
<x xml:space="preserve">Abstract</x> A questionnaire survey of all active population based cancer registries in sub‐Saharan Africa obtained information on their characteristics (size, staffing, funding), methods of working, the nature of any links between registries and their respective Health Authorities (national and/or local), and the use of their data in research or cancer control planning. 23/25 registries (92%) responded. Sources of direct funding and estimated amounts from each source were established, and suggest that it is approximately US$8‐9 per case registered. Almost half of the funding is used for routine data collection, processing and analysis. Staffing levels vary, partly as a function of the registry size (approximately one FTE per 300 cases registered). Most data collection is active, using multiple sources (median 10 per registry), and is largely paper‐based (abstraction onto paper forms), although all use the computer system CanReg© for data entry, storage and analysis. Most reporting by the registries is remarkably timely, and in general, their results are widely used by health authorities and other stakeholders in planning and evaluating services, while research output is much more variable. These registries are the source of almost all the existing information on cancer incidence and mortality in sub‐Saharan Africa, as published in IARC's "Globocan".